1975
DOI: 10.1111/j.1440-1681.1975.tb01852.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heart rate on indices of myocardial contractility in the dog

Abstract: 1. Changes in heart rate were evoked by atrial pacing in anaesthetized dogs with no pretreatment and in dogs given reserpine or guanethidine for 72 h. The effect of alterations in heart rate were related to two indices of myocardial contractility: the maximal rate of change of left ventricular pressure (dp/dt), and an index which was independent of initial fibre length (dp/dt)/IIT, where IIT is integrated isometric tension. 2. An increase in heart rate in control dogs was accompanied by a rise in both dp/dt an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Although these workers initially suggested that this reflected a possible difference between rate and contractility b-adrenoceptors, they later attributed it to the additional effects of blocking circulating catecholamines (Harry, Kappagoda, Linden & Snow, 1973). Increases in heart rate induced in the dog heart by pacing have been shown to cause a raised dP/dt max (Furnival et al, 1970;Barnes et al, 1973;Richmond, Angus, Goodman & Cobbin, 1975). The rat heart, however, is known to be unusual in that increases in rate of stimulation are accompanied by decreases in contractile force, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although these workers initially suggested that this reflected a possible difference between rate and contractility b-adrenoceptors, they later attributed it to the additional effects of blocking circulating catecholamines (Harry, Kappagoda, Linden & Snow, 1973). Increases in heart rate induced in the dog heart by pacing have been shown to cause a raised dP/dt max (Furnival et al, 1970;Barnes et al, 1973;Richmond, Angus, Goodman & Cobbin, 1975). The rat heart, however, is known to be unusual in that increases in rate of stimulation are accompanied by decreases in contractile force, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In the provided software, these beats can be identified and manually removed. Increased heart rate causes an increase in contractility (the Bowditch effect) (Balcazar et al, 2018; Richmond et al, 1975). In a physically inactive person this is due mainly to reduced parasympathetic drive.…”
Section: Introductionmentioning
confidence: 99%
“…in contractility (the Bowditch effect) (Balcazar et al, 2018;Richmond et al, 1975). In a physically inactive person this is due mainly to reduced parasympathetic drive.…”
Section: Introductionmentioning
confidence: 99%